Copper Nitrate‐Mediated Selective Difunctionalization of Alkenes: A Rapid Access to β‐Bromonitrates. Issue 9 (22nd March 2019) - Gao, Mingchun; Zhou, Kaijing; Xu, Bin
Abstract: A regioselective copper nitrate‐mediated difunctionalization of alkenes has been developed for the rapid synthesis of β‐bromonitrates, where copper nitrate is used as an ideal nitrooxy source for the first time and the products will find many applications in organic synthesis as versatile synthons. Different from the general reports that copper nitrate acts as the nitro source, the given protocol provides a direct access to functionalized nitrates, with operational simplicity, good functional group tolerance and a wide substrate scope. Abstract :